CLEAN WATER SERVICES OF REGIONAL DRINKING WATER COMPANIES (PDAM) IN LAMANGGA VILLAGE, BAUBAU CITY - Samsualam, Muhammad Sutan; Basir, Muh. Askal; Inzana, Nur (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
The Baubau City Regional Drinking Water Company (PDAM) is a BUMD company that facilitates and serves the clean water needs of residents of Lamangga Village, Baubau City. This study uses a qualitative methodology with a descriptive approach. This study uses public service theory with public service indicators being tangibles, reliability, responsiveness, assurance, and emphaty. The results of this study show that the services of the Baubau City Regional Drinking Water Company (PDAM) still need to be improved in terms of responding to and handling service problems, that the available facilities and infrastructure are still inadequate, the services felt by customers are still not served wholeheartedly. According to the findings of this study, the Baubau City Regional Drinking Water Company (PDAM) does not provide proper clean water services in Lamagga Village. The researcher suggested that when carrying out the services of the Baubau City Regional Drinking Water Company (PDAM), efforts should be maximized in terms of service to make it easier for customers to submit complaints or ask questions about services and infrastructure, this must be reconsidered for the convenience of customers.